Mathematical modeling of the profile of a gear cutting rolling tool for machining of non-involute gear wheels - Tretyak, T. E.; Gutsalenko, Yu. G.; Shelkovoi, A. N.; Mironenko, A. L.; Mironenko, S. A. (Editura "Academica Brâncuşi", Târgu Jiu, România, 2019)
In this article, the relevance of the study of gears with a complex non-involute profile of the tooth flanks is justified. For the subsequent study of non-involute gearings, the task of mathematical modeling of the profile of a gear-cutting rolling tool for machining of noninvolute gear wheels is solved. As a profile of the tooth flank of a rack, a certain section of one of the previously simulated flat kinematic curves is considered. Based on the algorithm for calculating the profile of envelope surfaces, a method for geometric analysis of the process of surfaces shaping by rolling gear cutting tools has been developed. Using computer graphics, the sequential shaping of the teeth space of non-involute gear wheels processed by rolling gear cutting tools with a given tooth profile was studied.
Keywords: shaping of gear wheels; mating surfaces; tooth profile; flat kinematic curve